Cx3cr1 deficiency aggravates Aβ driven neurodegeneration and cognitive decline in a mouse model of Alzheimer's disease. (20th December 2022) - Puntambekar, Shweta S; Moutinho, Miguel; Lin, Peter Bor‐Chian; Jadhav, Vaishnavi; Tumbleson‐Brink, Danika; Balaji, Ananya; Benito, Martin A; Xu, Guixiang; Oblak, Adrian L; Reeves, Cristian A Lasagna; Landreth, Gary E; Lamb, Bruce T
Abstract: Background: Despite its identification as a key checkpoint regulator of microglial activation in Alzheimer's disease, the overarching role of CX3CR1 signaling in modulating mechanisms of Aβ driven neurodegeneration, including accumulation of hyperphosphorylated tau in is not well understood. Method: Using 4 ‐ and 6‐month old 5xFAD;Cx3cr1+/+ and 5xFAD;Cx3cr1‐/‐ mice, we use immunohistochemistry, western blotting, transcriptomic analysis and quantitative real time PCR to investigate accumulation of soluble and insoluble Aβ species, plaque associated microglial activation, synaptic dysregulation and neurodegeneration with disease progression. Flow cytometry based, Aβ uptake assays are used for in‐vivo characterization of the effects of CX3CR1‐signaling on microglial phagocytosis and degradation of methoxy‐X04+ fibrillar Aβ. Lastly, we use Y‐maze testing to analyze the effects of Cx3cr1 deficiency on working memory in 5xFAD mice. Result: We show that disease progression in 5xFAD;Cx3cr1‐/‐ mice is characterized by increased deposition of filamentous plaques that display defective microglial plaque engagement, along with impaired microglial Aβ phagocytosis and lysosomal acidification in‐vivo. Interestingly, Cx3cr1 deficiency resulted in heighted accumulation of neurotoxic, oligomeric Aβ, which correlated with severe neuritic dystrophy, preferential loss of post‐synaptic densities, exacerbated tau pathology, neuronal loss and cognitive impairment. Transcriptomic analyses using cortical RNA coupled with real time PCR validation using FACS‐purified microglial cells revealed dysregulated TGFβ responses, inflammatory signaling and oxidative stress responses in 5xFAD;Cx3cr1‐/‐ mice. Conclusion: In contrast to increased Aβ uptake by Cx3cr1‐/‐ microglia during early disease, Cx3cr1 deficiency impairs microglial uptake and degradation of fibrillar Aβ, thereby triggering an accumulation of neurotoxic soluble and insoluble Aβ species with disease progression. Our results indicate that Aβ‐driven microglial dysfunction in Cx3cr1‐/‐ mice aggravates tau hyperphosphorylation, neurodegeneration, synaptic dysregulation and impairs working memory. This study underscores the importance of investigating the time‐dependent role of CX3CR1‐driven microglial responses in AD.